2017
DOI: 10.1016/j.jesp.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of socioeconomic mobility influence academic persistence among low socioeconomic status students

Abstract: In press at the Journal of Experimental Social Psychology Note: This document represents the accepted but pre-copyediting version of this article. Please refer to the published version (available soon) for the official final versions of all text, statistics, figures, and tables.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 65 publications
2
71
0
Order By: Relevance
“…The higher educational level of those responsible for the schoolchildren in the PrivG compared with that of those responsible for the students in the PubG (p<0.001), in addition to the difference in SES between the groups, which was higher in the PrivG (p<0.001), corroborate the conclusion by Von Stumm et al (19) , who reported that educational level positively influences the SES, that is, the higher the educational level of parents and/ or legal guardians, the higher the family SES. The opposite also seems to be true: family SES influences the educational level reached by its members.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher educational level of those responsible for the schoolchildren in the PrivG compared with that of those responsible for the students in the PubG (p<0.001), in addition to the difference in SES between the groups, which was higher in the PrivG (p<0.001), corroborate the conclusion by Von Stumm et al (19) , who reported that educational level positively influences the SES, that is, the higher the educational level of parents and/ or legal guardians, the higher the family SES. The opposite also seems to be true: family SES influences the educational level reached by its members.…”
Section: Discussionsupporting
confidence: 86%
“…According to Schoon et al (18) , the education network and the education attainment the individual vary according to academic performance: children with low school performance tend to achieve lower levels of education than children with good school performance. In contrast, educational level seems to have an influence on SES, health, and quality of life (19) . Motivation to study together with the incentive and academic assistance offered to students contribute positively to the socioeconomic mobility of families and, consequently, of the population (20) .…”
Section: Introductionmentioning
confidence: 92%
“…For example, Science News Staff (2018) found that many animals, plants, and bacteria use different resilience strategies when faced with scarce resources, predators, and other challenges, such as stealing genes or switching sex (Science News Staff, 2018). (Browman et al, 2017) found that despite all the disadvantages, many low socioeconomic status students still maintain high learning motivation and academic persistence. Therefore, resilience improves survival.…”
Section: Discussionmentioning
confidence: 99%
“…During both high school and college, students from lower-SES backgrounds who perceived more socioeconomic mobility (which is linked to thoughts about their own future identities) found more meaning in academic tasks and earned higher grades. In experiments, participants who were randomly assigned to encounter evidence of high rates of socioeconomic mobility showed a corresponding increase in academic persistence, compared with participants who encountered evidence of low mobility rates (Browman, Destin, Carswell, & Svoboda, 2017).…”
Section: Destinmentioning
confidence: 99%